The Americans - Julia, Raul.; Bull, Peter; Tovares, Joseph; Vecchione, Judith; WGBH (Television station : Boston, Mass.); Channel Four (Great Britain); Central Independent Television (South Burlington, VT : Annenberg/CPB Collection, 1993)
This program examines the impact that Hispanics in the United States are having on American society, culture and politics. It looks at three groups: Cuban in Miami, Puerto Ricans in New York City and Chicanos in Southern California.
Title on container: The Latin American and Caribbean presence in the U.S.
In English and Spanish, with English subtitles and voiceovers.
VHS format.
Raul Julia, narrator.
Keywords: Hispanic Americans; Cuban Americans -- Florida -- Miami; Puerto Ricans -- New York (State) -- New York; Mexican Americans -- California